2019
DOI: 10.35542/osf.io/xbm3t
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Analysis of College Choice Information Provided on Graduate Program Websites: Implications for Improving Applicant Diversity in Educational Measurement

Abstract: There has long been a concern about the lack of representation of ethnic minorities in the field of educational measurement. As previous research has shown that graduate programs primarily rely on their websites for recruiting efforts, the objective of this study was to conduct a content analysis of all U.S. educational measurement program websites to evaluate the availability of college choice information found to be useful for underrepresented ethnic minority applicants. In terms of program climate, results … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 13 publications
(25 reference statements)
0
14
0
Order By: Relevance
“…Measurement scholars have suggested that this shortage in measurement specialists can be attributed to, at least in part, the lack of ethnic minority recruitment in the field (Brennan & Plake, 1990; Sireci, 2000). Still increasing calls for a more diverse assessment community (Sireci, 2000; Rios, Randall, & Donnelly, 2019) have gone largely unanswered. To be sure, developing and maintaining a well‐trained and diverse pipeline of measurement specialists is critical to the field.…”
mentioning
confidence: 99%
“…Measurement scholars have suggested that this shortage in measurement specialists can be attributed to, at least in part, the lack of ethnic minority recruitment in the field (Brennan & Plake, 1990; Sireci, 2000). Still increasing calls for a more diverse assessment community (Sireci, 2000; Rios, Randall, & Donnelly, 2019) have gone largely unanswered. To be sure, developing and maintaining a well‐trained and diverse pipeline of measurement specialists is critical to the field.…”
mentioning
confidence: 99%
“…In their review of measurement program websites, Rios et al. (2019) found that only 16% of reviewed programs encourage diverse students to apply, and only 5% specifically encourage ethnically diverse students to apply. To support these efforts, they advocated for programs to portray their commitment to diversity through inclusion of a statement of support on their websites.…”
Section: Recruitment Questions Results and Implicationsmentioning
confidence: 99%
“…This shortage can be traced to sluggish enrollment and stagnant growth of graduate education programs. From 2007 to 2016, conferred doctorate degrees in “educational evaluation and research,” “educational statistics and research methods,” and “educational assessment, testing, and measurement” ranged from a low of 128 in 2012 to a high of 157 in 2015 (Rios, Randall, & Donnelly, 2019). Over the same period, growth in international student graduates far outpaced American students (Randall, Rios, & Jung, 2021a), meaning the percentage of new American qualified labor decreased.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations